Analisis Harga, Kualitas Pelayanan, dan Promosi Terhadap Kepuasan Pelanggan Rental Mobil pada CV. MAHKOTA Sidoarjo - Mokhammad Thoriq Al Khaq; Lilik Indayani; Vera Firdaus (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the influence of price, service quality, and promotion on customer satisfaction in the car rental services of CV. MAHKOTA in Sidoarjo. The research uses a quantitative approach with data collected through questionnaires distributed to 100 respondents who are customers of CV. MAHKOTA. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression analysis, and t and F tests with the help of SPSS 29. The results show that price, service quality, and promotion variables have a positive and significant influence on customer satisfaction both partially and simultaneously. The most dominant indicators are assurance (service quality), price competitiveness (price), and publicity through social media (promotion). These findings indicate that the three variables together explain 87.7% of the variation in customer satisfaction. Therefore, CV. MAHKOTA is advised to maintain competitive pricing strategies, enhance service reliability, and optimize digital promotion to increase customer satisfaction.